Comparing the effects of corn fermented protein with traditional distillers dried grains fed to healthy adult dogs on stool quality, nutrient digestibility, and palatability - Kilburn-Kappeler, Logan R.; Lema Almeida, Krystina A.; Paulk, Chad B.; Aldrich, Charles G. (Frontiers in Animal Science, 2023)
Traditional distillers dried grains, co-products from the ethanol industry, can be utilized as sustainable ingredients for pet food. However, negative consumer perception prevents their widespread use. Corn fermented protein (CFP) is produced using post-fermentation separation technology resulting in a high protein ingredient, which may increase consumer appeal. Therefore, the objective of this study was to compare the effect of CFP on stool quality, nutrient digestibility, and palatability to traditional distillers dried grains when fed to dogs. The control diet contained 15% soybean meal (CON) and experimental diets contained either 3.5% brewer's dried yeast (BDY), 2.5% brewer's dried yeast plus 17.5% distillers dried grains with solubles (BDY+DDGS), or 17.5% corn fermented protein (CFP). Experimental diets were fed to adult dogs (n = 12) in a 4 x 4 replicated Latin square design. Dogs were adapted to diets for 9 days followed by a 5-d total fecal collection. Titanium dioxide (0.4%) was added to all diets as an external marker to estimate digestibility. Data was analyzed using a mixed model in SAS with treatment as a fixed effect and dog and period as random effects. Fecal output was greatest (P < 0.05) for dogs fed BDY+DDGS. Feces were firmer (P < 0.05) for dogs consuming CFP compared to CON and BDY+DDGS. Overall, nutrient digestibility was greatest (P < 0.05) for CON and BDY and lowest for BDY+DDGS with CFP intermediate. There were no differences (P > 0.05) in total short chain or branched chain fatty acid concentrations in fresh fecal samples of dogs fed dietary treatments. However, percent propionate was greater (P < 0.05) in fecal samples of dogs fed CON compared to BDY+DDGS. Whereas percent valerate was greater (P < 0.05) in fecal samples of dogs fed CON compared to CFP. In the palatability evaluation, dogs had no preference when CON was compared to BDY or BDY+DDGS. However, dogs appeared to prefer CON over CFP. Overall, CFP resulted in improved stool quality and nutrient digestibility when compared to DDGS, which could increase consumer appeal for inclusion into pet food. Whereas the impact of CFP on palatability warrants further investigation.